Heavy metal contents in aquatic organisms from the estuary of Sungai Sarawak - Mohamad, Ariffin (Universiti Malaysia Sarawak (UNIMAS), 1998)
Three different classes of aquatic organisms and sediments from the estuary of Sg. Sarawak were analysed for heavy metal contents. Heavy metal contents were analysed quantitatively using the ICP-AES instrument located at the Geological Survey Malaysia, Sarawak. Standard preparation method from the MLS manual was used and the samples were digested using a microwave digester. The data revealed that there was an abundance amount of Mn in sediments and mollusca, The Mn contents in sediments from 5 stations ranges from 234.1 to 361.5 ug/g. In molluscs, Mn contents were the highest in Geloina sp. at 182.2 ug/g. Zinc were the highest in catfish liver/gut at 229.6 ug/g. Meanwhile, Cu and As contents were high in mangrove crab at 54.0 and 5.5 ug/g. These amount exceeds the maximum permitted proportion of 30 and 1 ug/g respectively (Food Act, 1983). Other metal contents were either low or in trace amounts. The studyshows that certain aquatic organisms are better at bioaccumulating and retaining metals than others.